THE EFFECTIVITY OF E-BRANDING IMPLEMENTATION WITH CRM CONCEPT ON INCREASED SALES AT CATERING BUSINESS IN PADANG CITY - Mutiana Pratiwi; Ulya Ilhami Arsyah (Jurnal Ipteks Terapan, 2020)
Micro, small and medium enterprises are a business sector that is very helpful in various aspects of theIndonesian economy. In the city of Padang has various types of SME businesses. One of them is Catering. Thedevelopment of the catering business in this city is very rapid because of the many people's interest in usingthese services. As a result, there was competition between businesses that showed a significant impact on thecatering business so that each of these businesses had to be able to create their own market by creating a brandfor their catering business. This research was conducted to determine the effectiveness of the implementation ofe-branding UKM Catering Padang City with the concept of CRM (Customer Relationship Management) toincrease sales. The results of this study are the determination of the effectiveness of e-branding that has beencarried out on the level of marketing and income obtained by SMEs, which have benefits as a form ofactualization of the character of the UKM Catering business and to support marketing so that sales increase andincrease competitiveness appears. The method used is Customer Relationship Management (CRM).